1999
DOI: 10.1111/j.1469-1795.1999.tb00045.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the population viability analysis packages GAPPS, INMAT, RAMAS and VORTEX for the whooping crane (Grus americana)

Abstract: Population viability analysis (PVA) is widely used in conservation biology to compare management strategies and predict probabilities of extinction for endangered species. However, it remains unclear whether the available range of generic PVA programs produce similar predictions when applied to common data sets. A comparative analysis was carried out using six commonly applied PVA packages (GAPPS, INMAT, RAMAS Age, RAMAS Metapop, RAMAS Stage and VORTEX), based on the extensive population data available for the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(26 citation statements)
references
References 29 publications
1
25
0
Order By: Relevance
“…It has been suggested that although a temporary shortage of males can greatly decrease the breeding rate and increase the extinction risk in monogamous species, this potentially important stochastic element can be ignored in polygamous species (Brook et al, 1999(Brook et al, , 2000a. However in our study, following OFY in importance, the SR also played an important role when predicting extinction risk.…”
Section: Sensitivity Analysismentioning
confidence: 53%
See 1 more Smart Citation
“…It has been suggested that although a temporary shortage of males can greatly decrease the breeding rate and increase the extinction risk in monogamous species, this potentially important stochastic element can be ignored in polygamous species (Brook et al, 1999(Brook et al, , 2000a. However in our study, following OFY in importance, the SR also played an important role when predicting extinction risk.…”
Section: Sensitivity Analysismentioning
confidence: 53%
“…In comparative studies of PVA programs, Vortex was shown to give an unbiased estimate of extinction risk for well-studied mammals and birds (Brook et al, 1999(Brook et al, , 2000bTian et al, 2011). A detailed description of the package and its features can be found in Miller and Lacy (2005).…”
Section: Pva Modelmentioning
confidence: 99%
“…Uncertainties concerning the predictive reliability of PVA have led to questioning the validity of conclusions drawn from some PVA [20]. However, PVA has proven useful when there is significant information about the species' vital rates [14,21].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, PVA may be useful to assess levels of threat when species with limited data are analyzed cautiously, taking into consideration model assumptions [22][23][24]. As many conservation actions and management options are currently based on PVA results, PVA predictions should be quantitatively reliable, whether the proposed actions are sufficient or not in order to achieve species recovery [15,20].…”
Section: Introductionmentioning
confidence: 99%
“…To successfully manage and conserve any wildlife species, a basic understanding of the population's structure and group dynamics are required [12][13][14][15]. Demographic parameters (i.e., vital rates) are often used as indices of population's health and stability, and to evaluate a species' status and viability [16,17]. These are commonly assessed using population models (e.g., VORTEX, RAMAS, ALEX) which rely on demographic data, such as sex ratio, fecundity, productivity, age structure, group size, and survival rate, to make temporal predictions [18,19].…”
Section: Introductionmentioning
confidence: 99%